A structural study of Si6‐ring‐containing [Si6Cl14]2− chlorosilicates. Issue 10 (1st October 2015) - Tillmann, Jan; Lerner, Hans‐Wolfram; Bolte, Michael
<x xml:space="preserve">Abstract</x> The crystal structures of four substituted‐ammonium dichloride dodecachlorohexasilanes are presented. Each is crystallized with a different cation and one of the structures contains a benzene solvent molecule: bis(tetraethylammonium) dichloride dodecachlorohexasilane, 2C8H20N+·2Cl−·Cl12Si6, (I), tetrabutylammonium tributylmethylammonium dichloride dodecachlorohexasilane, C16H36N+·C13H30N+·2Cl−·Cl12Si6, (II), bis(tetrabutylammonium) dichloride dodecachlorohexasilane benzene disolvate, 2C16H36N+·2Cl−·Cl12Si6·2C6H6, (III), and bis(benzyltriphenylphosphonium) dichloride dodecachlorohexasilane, 2C25H22P+·2Cl−·Cl12Si6, (IV). In all four structures, the dodecachlorohexasilane ring is located on a crystallographic centre of inversion. The geometry of the dichloride dodecachlorohexasilanes in the different structures is almost the same, irrespective of the cocrystallized cation and solvent. However, the crystal structure of the parent dodecachlorohexasilane molecule shows that this molecule adopts a chair conformation. In (IV), the P atom and the benzyl group of the cation are disordered over two sites, with a site‐occupation factor of 0.560 (5) for the major‐occupied site.